Regulating Doxing and Personal Data Dissemination in Indonesia - Halif Halif; Ainul Azizah; Prisma Diyah Ratrini (University of Jember, Indonesia, 2023)
The development of information technology have an impact on cyber crimes such as identity theft, fraud, and misuse of personal data. One of the crimes, abuse of personal data is doxing. It was an illegal act to spreading action people's personal information or data without permission and creates dangerous situations, humiliation, harassment, or other adverse which can lead to spoilage of the victims. The act of doxing or disseminating personal data has recently increased, especially among journalists. Doxing is a transmission system of personal data conducted by journalists legally. The freedom of journalists who compose and develop news to encourage misuse of personal data. In this case, we are interested in studying the legal basis of doxing and personal data dissemination in Indonesia, with the objectives: first, does the regulation of distributing personal data (doxing) in the Electronic Information and Transaction Law encounter the doxing typology? second How is the reformulation of the criminal law policy on the act of spreading personal data (doxing) in fulfilling the doxing typology? This research adopted normative legal research and used a statutory approach, conceptual approach, and comparative approach. The results showed that the act of doxing in the ITE Law does not regulate it according to the doxing typology. Therefore, there is a need to reform criminal law policies in the ITE. It can also be through the Bill of Personal Data Protection. The government must compose a regulation on disseminating personal data or doxing in the Law concerning Electronic Information and transactions.